Quality of Life of Adolescents and Young Adults After Testicular Prosthesis Surgery During Childhood: A Qualitative Study and Literature Review - Zoi Chantzi; Sotirios Fouzas; Alexandros Drivalos; Athanasia Stamati; Agapios Gkentzis; Maria Athanasopoulou; Katerina Kambouri; Despoina Gkentzi; Eirini Kostopoulou; Anastasia Vareli; Evangelos Blevrakis; Konstantinos Zachos; et al. (Children)
Background/Objectives: To evaluate the quality of life (QoL) of adolescent and young adult males who had testicular prosthesis surgery during their childhood, as well as their own and their parents’ inner perceptions and feelings. To our knowledge, this is the first qualitative study and one of few with an integrated approach on the QoL of pediatric testicular prosthesis recipients. Methods: Recipients and their parents were interviewed regarding their life with the testicular prosthesis. Major QoL domains (i.e., physical and mental health, interpersonal relationships, sexuality) were assessed. Results: Although there were participants who viewed the outcomes with negativity, most expressed satisfaction. Daily routine returned to normal after a postoperative period with precautions, such as fear of damaging either the implant or the healthy testis. Prosthesis feeling was acceptable and normalized with time, while self-image and self-confidence were boosted by the presence of the prosthesis. All participants outlined the importance of privacy as being kept in the inner family circle. Some exhibited introverted behavior. Regarding sentimental and sexual intimacy, the prosthesis produced anxiety and concern both in experienced recipients and minors, which was moderated by a normal scrotal appearance. Conclusions: Testicular prosthesis surgery performed from childhood to adulthood may create profound and variable concerns, which may affect the recipients and their companions in the long term. Therefore, it should not be considered in a simplistic manner as a routine procedure and should be preceded by thorough conversation with experts.